Changes in plasma levels of omentin-1, CRP and aerobic capacity after exercise interventions in overweight and obese women - Nasim Abbasifard; Vazgen Minasian (Shahid Beheshti University, 2019)
Purpose: The aim of this study was to evaluate the effect of two methods of aerobic and resistance training on plasma levels of omentin-1, CRP and aerobic capacity of overweight and obese women.Methods: Twenty-two overweight and obese women volunteered to participate in this study. They were randomly assigned in two groups of aerobic (Mean age: 40.64±7.76y, BMI: 30.40±4.94 kg/m2, body fat percent: 27.31%±2.98) and resistance exercises (Mean age: 40.91±6.82y, BMI: 31.69±4.81 kg/ m2, body fat percent: 26.94%±2.99). The aerobic training program included jogging and running activities with 55%-75HRmax for 30-60 minutes, 3 sessions a week, and resistance training included a weight training program with 75% 1RM for 3 sets and 3 sessions per week for eight weeks. Blood samples were collected before interventions and 24 hours after the last training session in a fasting condition.Results: The results showed eight weeks of aerobic and resistance training interventions caused significant decrease in C-reactive protein, and significant increase on Omentin-1 and aerobic capacity of both groups (p<0.001); but there were non-statistically significant differences between C-reactive protein, Omentin-1 levels and aerobic capacity of both groups (p>0.05).Conclusion: The results revealed the effectiveness of both aerobic and resistance training on C-reactive protein, Omentin-1 levels, and cardiorespiratory endurance of both groups. It seems that short term exercise interventions have similar effects on these metabolic indexes.